Combination chemotherapy in rodents: a model for chemotherapy-induced neuropathic pain and pharmacological screening - Akhilesh; Uniyal A.; Mehta A.; Tiwari V. (My University, 2025)
Chemotherapy-induced neuropathic pain (CINP) remains a therapeutic challenge, with no US-FDA approved drugs or effective treatments available. Despite significant progress in unravelling the pathophysiology of CINP, the clinical translation of this knowledge into tangible outcome remains elusive. Here, we employed behavioural and pharmacological approaches to establish and validate a novel combination-based chemotherapeutic model of peripheral neuropathy. Male Sprague Dawley rats were subjected to chemotherapy administration followed by assessment of pain behaviour at different time-points post-chemotherapy. Paclitaxel-treated animals displayed an enhanced thermal and mechanical hypersensitivity from day four onwards which continued till day thirty-five post last paclitaxel injection. Notably, rats subjected to combination chemotherapy, displayed prolonged hypersensitivity that emerged on day four and persisted until day fifty-six. RT-PCR analysis revealed significant upregulation in DRG and spinal mRNA expressions of TRP channels (TRPA1, TRPV1, & TRPM8), pro-inflammatory cytokines (TNF-α & IL-1β) and neuropeptides, Substance P and CGRP in both the pain models. Interestingly, the combination chemotherapy model demonstrated a significant increase in DRG and spinal NR2B expressions compared to rats solely treated with paclitaxel. Pharmacological investigations revealed that gabapentin treatment substantially mitigates pain hypersensitivity in both the combined chemotherapy and paclitaxel-administered groups, with the simultaneous reversal of cellular and molecular changes observed in the lumbar DRG and spinal cord of rats. The findings from this study suggests that combination chemotherapy model exhibits heightened and prolonged hypersensitivity in comparison to the conventional paclitaxel-induced neuropathic pain model. This model not only recapitulates clinical biomarkers of neuropathy but also presents a potential alternative platform for screening analgesic drugs targeted at CINP. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.